Warisan Al-Attas: Menghidupkan Kembali Islamisasi Ilmu untuk Pendidikan Masa Depan - Adhimas Alifian Yuwono; Abid Nurhuda (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2024)
Modern Islamic education must be realised to maintain the existence and purity of Islamic science. The purpose of this research is to discuss the efforts to realise modern Islamic education by understanding the concept of Islamisation of Science offered by Syed Muhammad Nauqib Al-Attas. This type of research is literature, which discusses the thoughts of figures, using heuristic approaches and inherent coherence. The analysis technique used is this analysis, by examining primary sources from the book by Syed Muhammad Nauqib Al-Attas and narrating them, then looking for relevance. The results of this study indicate that, Islamisation of Science in education is the inclusion of key concepts which include the concepts of religion (din), human (Insan), wisdom (hikmah), justice (‘adl), charity (’amal as adab), science ('ilm), and university (Kuliyyah jami'ah). This concept must be conserved in the modern Islamic education to maintain the existence and purity of Islamic science.